A Comparative Study of the Composition of Discs and of Proteoglycans from Different Spinal Levels of Sheep - Melrose, J.; Ghosh, P.; Taylor, T. K. F.; McAuley, Louise (Veterinary and Comparative Orthopaedics and Traumatology, 1994)
Compositional analyses were undertaken on lumbar (L2L3 - L5L6) and lumbosacral (L6S1) intervertebral disc tissues from young adult (2-year-old) merino wethers. The proteoglycan level in the nucleus pulposus of the lumbosacral disc was significantly lower than that found in the nucleus pulposus of lumbar levels (p<0.05). The annulus fibrosus was richer in collagen compared to the nucleus pulposus in all discs examined, and the lumbosacral disc consistently had both higher annulus fibrosus and nucleus pulposus collagen levels than lumbar discs (p<0.05). Aggregation of the high buoyant density proteoglycans, with hyaluronic acid, was generally higher in annulus fibrosus proteogly-cans than nucleus pulposus proteogly-cans irrespective of the spinal level examined. Examination of the inter-vertebral disc proteoglycans, by composite agarose polyacrylamide gel electrophoresis, demonstrated three proteoglycan subpopulations and that the nucleus pulposus generally contained a greater proportion of higher mobility more polydisperse proteoglycan species than the annulus fibrosus.Ovine intervertebral disc collagen and proteoglycan composition varies with spinal level. Lumbosacral intervertebral discs contain greater levels of non-aggregatable more polydisperse proteoglycan species than lumbar discs, which may reflect their relative proximities to the pelvis and the variable levels of stress experienced by the respective tissues.
Keywords: Intervertebral disc; proteoglycan heterogeneity; ovine disc